1997
DOI: 10.1037/0893-164x.11.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Treatment retention and follow-up outcomes in the Drug Abuse Treatment Outcome Study (DATOS).

Abstract: Clients in the national Drug Abuse Treatment Outcome Study reported significant overall improvements in drug use and related measures during a 12-month follow-up period. A quasi-experimental design was used to examine the relationship of treatment duration with outcomes in each of the 3 major modalities represented. Client subsamples with longer retention in long-term residential programs and in outpatient methadone treatment had significantly better outcomes than those with shorter lengths of stay (results we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
291
1
6

Year Published

1999
1999
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 456 publications
(312 citation statements)
references
References 42 publications
14
291
1
6
Order By: Relevance
“…For example, a series of articles by Lowenkamp and Latessa (2005) and Lowenkamp, Latessa, and Holsinger (2006) and a recent edition of Crime & Delinquency (Taxman & Marlowe, 2006) highlighted how the use of actuarial risk screening tools can be used to identify offenders who are more likely to benefit from placement in structured correctional and/or SA treatment programs. Research had found that programs and services lasting 90 days or longer increase the likelihood of effectiveness and promote lasting change for offenders (Hser et al, 2001;Hubbard et al, 1989;Simpson, Joe, & Brown, 1997), making it another useful measure of quality. The inclusion of SA as part of correctional treatment was selected because of the prevalence of substance use and/or abuse among offenders.…”
Section: Methods: the Ncjtp Surveymentioning
confidence: 99%
“…For example, a series of articles by Lowenkamp and Latessa (2005) and Lowenkamp, Latessa, and Holsinger (2006) and a recent edition of Crime & Delinquency (Taxman & Marlowe, 2006) highlighted how the use of actuarial risk screening tools can be used to identify offenders who are more likely to benefit from placement in structured correctional and/or SA treatment programs. Research had found that programs and services lasting 90 days or longer increase the likelihood of effectiveness and promote lasting change for offenders (Hser et al, 2001;Hubbard et al, 1989;Simpson, Joe, & Brown, 1997), making it another useful measure of quality. The inclusion of SA as part of correctional treatment was selected because of the prevalence of substance use and/or abuse among offenders.…”
Section: Methods: the Ncjtp Surveymentioning
confidence: 99%
“…The major goal of the therapeutic community is to encourage and support social learning, which fosters changes in behavior and attitude and the more elusive phenomenon of change in world view and self-image (De Leon, 2000). Studies have shown that individuals who complete therapeutic community treatment have lower levels of substance use, criminal behavior, unemployment, and depression than they had prior to treatment (Martin, Butzin, Saum, & Inciardi, 1999;Simpson, Joe, & Brown, 1997;Simpson, Joe, Fletcher, Hubbard, & Anglin, 1999;Wexler, Melnick, Lower, & Peters, 1999).…”
Section: Therapeutic Communitiesmentioning
confidence: 99%
“…Over the ensuing fifteen years researchers have echoed that key components of correctional and substance abuse programs for offenders generally fall into three areas: assessment and treatment matching, program services and content, and compliance management. Key elements of effective programs include (Fletcher & Chandler, 2006): standardized substance abuse assessment tool(s) for assessing severity of substance abuse disorder (Peters & Wexler, 2005); standardized risk assessment tool(s) to identify the appropriate clients for services (with a preference for high risk offenders being placed in services (Thanner & Taxman, 2003;Lowenkamp, Latessa, & Hoslinger, 2006;Andrews & Bonta, 1996;Taxman & Thanner, 2006;Taxman & Marlowe, 2006); interventions to engage the offender in treatment services and motivate him/her for change (Simpson, 2004); treatment orientations that employ therapeutic community, cognitive behavioral, or standardized behavioral modification techniques (Andrews, et al, 1990;Sherman, et al, 1997;Mackenzie, 2000); comprehensive services that address co-occurring medical and psychosocial disorders (Friedmann, Saitz, & Samet, 2003,McLellan, Arndt, Metzger, Woody, & O'Brien, 1993; family involvement in treatment (O'Farrell, 1993); treatment duration of 90 or more days (Hubbard et al, 1989,Simpson, Joe, & Brown, 1997; systems integration and a continuum of care (including aftercare) as the offender moves through different phases of the criminal justice system (Butzin, Martin, & Inciardi, 2002,Taxman & Bouffard, 2000; routine drug testing to monitor treatment progress (Sherman, et al, 1997); and use of sanctions and incentives to improve program retention or use of reinforcement schedules (Taxman, Soule, & Gelb, 1999;Marlowe & Kirby, 1999;Higgins et al, 1994).…”
Section: Introductionmentioning
confidence: 99%